Analysis Impact of Electric Vehicles on the Environment - Saputra, Dicky Wahyu Eko; Brillianti, Dani Fitria (Kirana Publisher (KNPub), 2024)
Many people use conventional vehicles because,they cause a lot of air pollution which makes the air polluted. That is why electric vehicles are made that can reduce air pollution. These electric vehicles use lithium batteries which do not emit carbon monoxide which can pollute the environment. . therefore, the indonesian government is intensively conducting outreach among the public so that they can buy electric vehicles to better protect the environment and not be contaminated by pollution caused by conventional vehicles. The primary goal of this study is to analyze the impact of electric vehicles (evs) on environmental pollution, with a focus on the role of evs in mitigating air pollution caused by conventional vehicles. Specifically, the study aims to consider the environmental benefits of shifting from conventional vehicles to electric vehicles evaluate the potential reduction in greenhouse gas emissions by introducing electric vehicles.assess the indonesian government's efforts and policies in promoting the spread of electric vehicles and understand the effectiveness of evs in raising public awareness. This study uses a mixed-method approach, combining quantitative and qualitative data. The primary methods include:literature review: reviewing existing research on ev emissions, the impact of battery production, and government policies regarding ev adoption.data analysis: analyzing air pollution data from traditional vehicle exhausts and comparing it with emissions data from electric vehicles, including life-cycle analysis of lithium batteries.surveys/interviews: conducting surveys or interviews with current ev users and potential ev buyers in indonesia to gather opinions, perceptions, and concerns regarding evs.policy analysis: reviewing indonesian government policies and evaluating incentives, subsidies, and other efforts to encourage ev adoption.